2010
DOI: 10.1159/000277593
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Patients with High-Risk Prostate Cancer following Radical Prostatectomy and Stage-Dependent Adjuvant Androgen Deprivation

Abstract: Purpose: To present the long-term outcome of high-risk prostate cancer patients treated by radical retropubic prostatectomy (RRP) and stage-dependent adjuvant androgen deprivation therapy. Patients and Methods: Between 1989 and 2005, 2,655 patients underwent RRP by 9 surgeons. All cases (n = 372) with high-risk prostate cancer (serum PSA >20 ng/ml, and/or clinical stage T2c or greater, and/or biopsy Gleason score 8 or greater) were identified and analyzed retrospectively. Results: At 5 and 10 years, cancer-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 55 publications
(27 reference statements)
1
17
0
1
Order By: Relevance
“…22 Multimodal intervention with surgery with or without adjuvant radiation therapy has shown great promise for such tumors, decreasing cancer specific mortality to 8% to 13% at 10 years. 23,24 Such a tradeoff may be worth the risk of the morbidity of aggressive treatment even in the face of a moderate risk of other cause mortality. Therefore, we advocate using tumor risk and life expectancy to triage treatment at the time of the treatment decision and not before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…22 Multimodal intervention with surgery with or without adjuvant radiation therapy has shown great promise for such tumors, decreasing cancer specific mortality to 8% to 13% at 10 years. 23,24 Such a tradeoff may be worth the risk of the morbidity of aggressive treatment even in the face of a moderate risk of other cause mortality. Therefore, we advocate using tumor risk and life expectancy to triage treatment at the time of the treatment decision and not before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one third to one half of patients suffer from biochemical relapse (BCR) within 5–10 years after primary curative prostatectomy or radiotherapy (RT) [24]. Salvage radiotherapy (SRT) is recommended in patients treated with radical prostatectomy who experience BCR without distant metastases [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…The median Gleason score from the prostate biopsy was 8 (range 6–10) and from the prostatectomy specimen 9 [79]. Only in 44% Gleason score of prostate biopsy and specimen was identical; underestimation in prostate biopsy score of one to three points was detected in 41% of patients and overestimation of one score point in 15%.…”
Section: Resultsmentioning
confidence: 99%
“…Using the same series, Gontero et al found that the PSA level was of prognostic relevance with 26% cured by surgery alone when PSA was 20–50 ng/mL but only about 7–9% with PSA >50 ng/mL [8]. A single-centre analysis of more than 2 600 patients with locally advanced prostate cancer after RP and adjuvant androgen deprivation revealed the Gleason score to be the most important prognostic factor [9]. In our much smaller series we did not attempt to show cancer-specific survival, but for the prediction of T stage and lymph node involvement, the Gleason score was not the most obvious parameter.…”
Section: Resultsmentioning
confidence: 99%